Diterpenoids from the Wood of Cunninghamia konishii. Issue 12 (December 2013) - Chen, Yu‐Chang; Li, Yen‐Cheng; Chiu, Hsi‐Lin; Cheng, Wei‐Yi; Hong, Yong‐Han; Sung, Ping‐Jyun; Kuo, Ching‐Chuan; Wu, Bor‐Tsang; Kuo, Yueh‐Hsiung
Abstract Investigation of the wood of Cunninghamia konishii resulted in the isolation and characterization of one new abietane diterpenoid, (6α, 7β)‐7, 8‐epoxy‐6‐hydroxyabieta‐9(11), 13‐dien‐12‐one (1), and two new labdane diterpenoids, (12R)‐12‐hydroxylabda‐8(17), 13(16), 14‐trien‐19‐oic acid (2) and (12R)‐12‐hydroxylabda‐8(17), 13(16), 14‐trien‐18‐oic acid (3). The structures of these new compounds were elucidated by analysis of their spectroscopic data.